Sustainable Business Performance for Local Business Development: Evidence from Indonesia Coffee Shops - Aprilia, Anisa; Fitrotul Laili; Putri Budi Setyowati; Adella Rania Salsabilah; Ivonia Indah Armasari (HABITAT, 2023)
Drawing on the concept of sustainable business performance, this study proposes a research model to investigate how variables such as digital organizational culture, organizational learning culture, ethical sensitivity, and access to finance contribute to the formation of a business performance model that is expected to contribute to long-term business performance in local industries dominated by coffee shops. The measure of sustainable business performance is the performance of economic, social, and environmental factors. The PLS-SEM approach was utilized to estimate this investigation's sustainable business performance model. The study examined 111 coffee shop owners, managers, and employees, selected based on their present position within the company, using a questionnaire distributed between July and November 2021. Several factors, including the organizational learning culture, the digital organizational culture, ethical awareness, and financial access, significantly influence the long-term financial performance of the coffee shop's business. This study contributes to the existing theory and the existing body of literature on topics such as the importance of ethical awareness, access to finance, digital organizational culture, and organizational learning culture. To improve overall business performance, business owners, managers, and even employees should examine the role that sustainable company performance plays in the development of each human resource's talents.